(untitled) (MMIT Proceedings, 2025)
This article examines the features of organizing physical education lessons within the framework of inclusive education. It explores scientific and methodological approaches that ensure the effectiveness of the pedagogical process involving students with special educational needs. The author emphasizes the importance of individualization, content adaptation, and the application of modern pedagogical technologies to achieve equal educational opportunities